Ecoutourism Zone of Coastal Conservation Area through Landscape Ecology Approach in Katingan Kuala Sub-regency, Katingan Regency, Central Kalimantan Province - Cakra Birawa; Raden Mas Sukarna (Jurnal Ilmu Kehutanan)
Marine and coastal areas as well as their natural resources have strategic effects towards the economic development of Indonesia because they are reliable to be one of the pillars of the national economy. Utilization and management of coastal areas either conducted by the community or local government have not reflect the conservation and sustainable aspects. To support these conditions, it is necessary to develop ecotourism zone, which is able to improve the local economies. This research aimed to study ecotourism zone of the coastal conservation area in Katingan Kuala Sub-district, Central Kalimantan Province through landscape ecology approach. The results showed that the total area of Katingan Kuala Sub-district, which is1,440 km2, could be categorized into four sub-zones, i.e. ecotourism zone is ±15.83 %, buffer zone is ± 31.30 %, core zone for conservation and rehabilitation is ± 29.55 %, and production and economic zone is ± 23.31 %. It was concluded that ecotourism development in these coastal areas should be in harmony with the conservation, protection, and preservation of the environment as a whole.